Bacterial NanoCellulose A Sophisticated Multifunctional Material - Gama, Miguel; Gatenholm, Paul; Klemm, Dieter (Taylor & Francis, 2012)
Bacterial nanocellulose (BNC) is an emerging nanomaterial with unique properties produced by several species of ubiquitous fermentation bacteria, most importantly Gluconacetobacter xylinus, previously known as Acetobacter xylinum. BNC has been used for a variety of commercial applications including textiles, cosmetics, and food products, and it has a high potential for medical applications. Bacterial NanoCellulose: A Sophisticated Multifunctional Material provides the state of the art of scientific knowledge about the mechanism of cellulose production by bacteria along with pointing out challenges in expansion of BNC production in large scale. It provides the latest update on BNC structure and its modification, as well as comprehensive information about current and future applications of BNC. This seminal work covers the basic science, technology, and economic impact of this bulk chemical as well as the companies and patents that are driving the field. It reviews the biosynthesis and properties of BNC.